A study of racial identity and the dispositions of student teachers - Sprott, Katherine R C (Kansas State University, 2007)
Growth in the percentage of students of color and English Language Learners in the nation's public schools has significant implications for teacher preparation institutions and professional development programs. Teachers and students alike gain immeasurable benefits from the process that requires them to get in touch with their own cultural, racial, and ethnic heritage. However, little is known about the racial identity of student teachers and the relationship of their dispositions to meet the needs of diverse learners. This study examines that issue at a large Midwestern University in a survey of 128 elementary and secondary student teachers. They completed "A Survey of Racial Identity and Dispositions of Student Teachers." The survey had three sections: "Demographics," "Racial Identity Status Self Assessment (RISSA)," and "Dispositions" self-rate their racial identity and dispositions regarding educational practices for diverse learners. Descriptive statistics were organized and reported for all data sets. T-test, multivariate analysis of variance (MANOVA), analysis of variance (ANOVA), regression analysis, and correlations were conducted. Results indicate that the student teachers had low levels of racial identity and that they are unaware of themselves as racial beings. Moreover, students reporting a low racial identity status tend to lack the knowledge of meeting the needs of diverse learners. As student teachers continued to increase in the number of multicultural college credit hours, their racial identity status increased. Thus, the number of enrolled multicultural hours uniquely predicted racial identity status level of the student teachers. Some other main findings included a higher rating by females than males on the RISSA and on meeting the needs of diverse learners. Non-Whites scored higher than Whites on the RISSA, and elementary student teachers tended to score higher than secondary on the RISSA. Recommendations for practice include assessing student teachers racial identity before entering the teacher preparation program, requiring more multicultural college credit hours, and utilizing simulations during preservice preparation. Recommendations for further study include duplicating the study at a historical Black university, replicating the study nationwide, and adding qualitative components to add depth to the data.
Keywords: Racial Identity and dispositions; Student teachers; Education, Curriculum and Instruction (0727); Education, Elementary (0524); Education, Higher (0745)